PEMBAYARAN GANTI RUGI BAGI KORBAN JARIMAH JINAYAT MENURUT PERSPEKTIF PRAKTISI HUKUM KOTA LANGSA - AZ, Nairazi (IAIN Langsa, 2019)
Providing compensation to victims should not be subject to administrative requirements, and baitul mall distributes based on decisions made by judges. In the case of diyat, both murder and rape are the authority of the victim and not the judge. In the Criminal Code, criminal offenses are regulated regarding compensation, but the amount of compensation received by victims is only a maximum of Rp. 2,500,000. The form of fines paid by the perpetrators should no longer go into the state treasury, but the fines are given to victims. As for the rape that was tried by the Langsa City Syar'iyah Court, it occurred in 2016. And in the victim's claim set forth by the Public Prosecutor, there were no claims made in the file regarding the matter of compensation, and the judge could not have decided on a cases that have no claim, because it can be said to be ultra petita. As for the implementation of ta'zir uqubat payment in Baitul Mal Qanun No. 10 of 2018, technical payments are made by opening a special regional account to receive the ta'zir funds. However, until now, the Langsa City Government has not instructed the Baitul Mal to open the account, because the Technical Guidelines on this matter have not been regulated in detail either through Pergub or Perwal.